Evaluating the Performance of a Photovoltaic System Using Acceptance Ration (AR) - Lazarina Mariana; Mohamad Nor, Ahmad Fateh (Journal of Quranic Sciences and Research, 2023)
The use of fossil fuels for energy production has several negative impacts on the environment and human health. Therefore, renewable energy is needed as an environmentally friendly source. Solar energy is one of the renewable energy produced from solar radiation using photovoltaic (PV). The explanations given by science about how the sun works are in line with what is stated in the Qur'an. One verse in the Quran speaks of Allah's Greatness and His Mercy, and it is found in: “And there He created a shining moon and made the sun a (brilliant) lamp. (Q.S. Nuh: 16)”. However, one of the problems in using PV systems is that the energy produced is unstable because it is influenced by the environment. Therefore, it is necessary to evaluate the performance of the PV system from time to time. In this research, the performance of the PV system is being done by determining the Acceptance Ratio (AR). AR is used to define the ratio of actual AC power to expected AC power. The largest expected output power value is 436.4788 W, on May 26. The acceptance ratio (AR) obtained ranges from 0.921 to 0.982, which should be worth approximately 0.9. This is influenced by the output power generated and the expected AC power generation data obtained from the calculation. The expected AC power generation value is different for each data depending on the weather conditions whether it is cloudy or sunny.